How Ecotheological Beliefs Vary Among Australian Churchgoers and Consequences for Environmental Attitudes and Behaviors - Pepper, Miriam (Review of religious research, 2016)
Worldviews play an important part in shaping and driving people's more specific environmental attitudes and behaviors. In a religious context, attention to eco(theo)logical worldviews, defined as foundational beliefs about the relationships between God, the Earth and humanity, helps researchers and environmental practitioners alike to better understand the religious frameworks which may foster or impede environmental action. This study draws on data from the 2011 Australian National Church Life Survey to examine churchgoers' beliefs about the presence of God in nature and human dominion over the environment. Australian churchgoers strongly affirmed the presence of God in the natural world, but were less affirming of dominion theology. Dominion varied between church traditions, but beliefs about the presence of God did not. The beliefs predicted a range of measures of environmental attitudes and behaviors. The results regarding dominion are consistent with findings from other countries, and the research extends previous limited work on the sanctification of nature to a concept of the presence of God in the natural world.